A Simple Economical Method for Assay of Atherogenic Small Dense Low-Density Lipoprotein-Cholesterol (sdLDL-C) - Renjith, R. S. (Springer-Verlag, 2011)
In the present study, we report a simple and economical precipitation method for the quantitative determination of small, dense LDL-cholesterol (sdLDL-C) in serum that is considered to be an emerging risk factor for cardiovascular disease. This method consisted of precipitation of lipoproteins of density <1.044 g/ml using heparin-MnCl(2) and quantification of cholesterol existed in the supernatant using reagents for routine cholesterol assay instead of the costly direct low density lipoprotein-cholesterol assay kit. The supernatant contained sdLDL and high-density lipoprotein (HDL) that was confirmed by polyacrylamide gel electrophoresis. sdLDL-C concentration can be calculated by subtracting the HDL-C value from the total cholesterol concentration of the supernatant. sdLDL-C values obtained by this modified method were similar to those obtained by direct assay of sdLDL-C and there was significant correlation between the two methods. In conclusion, this method is highly economical, do not require special equipments and is useful to evaluate atherogenic risk.